Regional innovation systems in Portugal: A critical evaluation - Santos, Domingos (2018)
Submitted by Domingos Santos (domingos.santos@ipcb.pt) on 2018-09-24T20:50:56Z No. of bitstreams: 1 Abstract_RIS_DS.pdf: 5497 bytes, checksum: f48f6a8bf51bbfb0d0c60ed66f9a69f9 (MD5)